Total Polyphenol content and antioxidant activities of Zizyphus Mauritiana Lam - M. Bakhir , Nornaemah; Osman , Hasnah; Abdul Hamid, Shafida (2008)
Evaluate total Polyphenol content and antioxidant activities of the methanol extract Zizyphus Mauritiana Lam. The total Polyphenol content in Z. Mauritiana leaves and twigs are 97.75 mg/g and 26.92 mg/g catechin respectively. The antioxidant activities were measured by 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay and 2,2'-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) radical cation (ABTS) assay using catechin, quercetin, and butylated hydroxytoluene (BHT) as references. The DPPH assay showed that the scavenging effect increased with increasing concentration used in the test samples.